ARAH PERKEMBANGAN AJARAN THEOSOFI ISLAM DALAM LITERATUR SASTRA PUJANGGA JAWA (PENDEKATAN GENEALOGI) (Dialogia, 2012)
Abstract: Islamic theosophy had developed in the literature of Palace poet in the form of Serat, Suluk, Primbon, Wirid and can even be found also in tembang mocopat, Chronicle, and puppet script. Academic studies of the literary legacy of the Palace poets are synchronous. Consequently, they can not answer the questions related to the contextual dynamics of the text. Thus, it is necessary to conduct the diachronic, genealogical, and historical study to fill the gap. The paper tried to answer the question of the direction of thought of Islamic theosophy developed by the Javanese poet. The evidences found in this study showed that the poets led to javanization of the concept of Islamic theosophy. Theosofi Islam berkembang dalam literatur Pujangga Keraton dalam Bentuk Serat, Suluk, Primbon, Wirid dan bahkan dapat ditemukan pula dalam tembang mocopat, Babad maupun  naskah pewayangan. Kajian-kajian akademis terhadap warisan sastra Pujangga tersebut bersifat sinkronis. Akibatnya, kajian-kajian itu tidak bisa menjawab pertanyaan terkait dengan dinamika kontekstual dari teks tersebut. Untuk itu, diperlukan kajian genealogi yang diakronis dan menyejarah. Tema yang dikemukakan pada makalah  ini mempetanyakan ke mana arah pemikiran theosofi Islam yang dikembangkan para Pujangga Jawa. Hasilnya menunjukkan bahwa para Pujangga mendorong konsep Theosofi Islam ke arah Jawanisasi Islam, dengan beberapa bukti yang ditemukan. Keywords: theosofi Islam, Jawanisasi Islam, genealogi, Pujangga